(untitled) (Revista de Ciências Agroveterinárias, 2016)
The productivity and quality of maize can be influenced by the occurrence of diseases. The intensity is affected by environmental factors and phytotechnical practices. Thus, this study was carried out to evaluate the effect of arrangement of plants and plant density on grain yield and thousand grain weight and incidence of stalk rot and fungi associated with grains. The work was conducted during the 2010/2011 and 2012/2013 seasons in Chapecó, SC, Brazil. The treatments consisted of different row spacings (0.45 and 0.80 m) and plant densities (50, 60, 70, 80 and 90 thousand plants ha-1) with a design of randomized blocks in subdivided sub plots. In the main plot two simple hybrids of corn early cycle were tested (P30F53H and DKB 240H), the subplots and the spacing in the sub-subplot plant populations. The experimental units consisted of six lines of 4 m in length. The yield on the 0.45 m spacing was 29.65% higher than in the 0.80 m spacing for the studied hybrids. The mass of a thousand grains and the incidence of rot grains decreased with an increase in plant population. However, the incidence of Fusarium verticillioides, Fusarium graminearum and Stenocarpella maydis was not affected by plant populations or by spacing tested under the conditions of this study.